Using a combination of human insights and 'deep learning' for real-time disaster communication. (July 2019) - Robertson, Brett W.; Johnson, Matthew; Murthy, Dhiraj; Smith, William Roth; Stephens, Keri K.
Abstract: Using social media during natural disasters has become commonplace globally. In the U.S., public social media platforms are often a go-to because people believe: the 9-1-1 system becomes overloaded during emergencies and that first responders will see their posts. While social media requests may help save lives, these posts are difficult to find because there is more noise on public social media than clear signals of who needs help. This study compares human-coded images posted during 2017's Hurricane Harvey to machine-learned 'deep learning' classification methods. Our framework for feature extraction uses the VGG-16 convolutional neural network/multilayer perceptron classifiers for classifying the urgency and time period for a given image. We find that our qualitative results showcase that unique disaster experiences are not always captured through machine-learned methods. These methods work together to parse through the high levels of non-relevant content on social media to find relevant content and requests.